INVENTORY CONTROL OF DISPOSABLE MEDICAL DEVICES IN HOSPITALS USING THE ECONOMIC ORDER QUANTITY (EOQ) AND REORDER POINT (ROP) METHOD - Elis, Elis Citra; Husein, Ismail (ZERO: Jurnal Sains, Matematika dan Terapan, 2023)
Controlling the supply of disposable medical devices at RSUD Dr. Pringadi not completely running well. The purpose of this research is to control the supply of disposable medical devices in order to determine the amount optimal ordering and to find out the number of reorders on all types of disposable medical devices. In this research also did calculating the value of the investment in each type. Calculation results for the investment level group of 0-70% has 11 types of disposable medical devices with a financial value of IDR 64,136,040.00 or 70% of the total investment with Economic Order Quantity can be ordered from a total of 14-152 items, Buffer Stock or safety stock starts stocking from 1-198 items and Reorders Points range from 1-318 items. For the investment level group 71-90% have 21 types of disposable medical devices with a financial value of Rp 181,953,529.00 or 20% of the total investment with EOQ can be ordered from quantity 2-21237item, buffer stock from 2-1237item and ROP from reordered 4-1987item.For the investment level group of 91-100% has 71 types of disposable medical devices with a financial value of Rp 85,103,749.00 or 9.4% of the total investment with EOQ calculations ordered starting from 1-421, buffer stock starting from 2-247 items and ROP starting from 2 - 397items.So this research is useful to help the warehouse Pharmacist at RSUD Dr. Pringadi in controlling the supply of medical devices disposable.